Oxidative stress linked to changes of cholinesterase and adenosine deaminase activities in experimentally infected chicken chicks with Eimeria spp - Griss L.G.* (2019)
© 2019 Elsevier B.V.Both oxidative stress and alterations in adenosinergic and cholinergic systems participate in initiation and progression of parasitic infectious diseases. Nevertheless, the involvement of these pathways during eimeriosis remains poorly understood. Therefore, the aim of this study was to evaluate the involvement of adenosinergic and cholinergic systems in regulation of inflammatory response and oxidative stress in chicken chicks experimentally infected with Eimeria spp. Two groups were formed for comparison at 3 time points (days 5, 10 and 15) of infection (PI): uninfected (control) and infected. Erythrocyte counts, hematocrit and hemoglobin levels were lower in infected chicks on day 15 post-infection (PI). Total leukocytes, heterophil and lymphocyte counts were higher in infected chicks on days 5 and 10 PI, while eosinophil counts were higher only on day 10 PI. Serum levels of total protein and globulins were higher in infected chicks on days 10 and 15 PI, while triglycerides and cholesterol levels were lower on day 15 PI. Acetylcholinesterase activity in total blood and butyrylcholinesterase activity in serum were higher in infected chicks on day 15 PI, while adenosine deaminase activity was higher on day 10 PI and lower on day 15 PI compared with the respective control. Finally, serum levels of reactive oxygen species and catalase activity in total blood were higher in infected chicks on day 15 PI, while superoxide dismutase activity in total blood was lower at the same time of infection. These data suggest that cholinergic and adenosinergic systems display a pro-inflammatory profile that contributes to impairment of immune and inflammatory responses in a mixed Eimeria infection. Furthermore, oxidative stress may contribute to clinical signs of disease as well as to pathogenesis. In summary, the impairment of immune response and alterations in blood antioxidant/oxidant status contributes to disease pathophysiology.